Midterm Outcomes of Crosslinked Acellular Bovine Jugular Vein Conduit for Right Ventricular Outflow Tract Reconstruction - Qian, Tao; Wu, Zhong-Shi; Hu, Jian-Guo; Yang, Yi-Feng; Wu, Qin; Lu, Ting; Huang, Can; Li, Jia (Frontiers in Pediatrics, 2021)
Objectives: Conduits for reconstructing right ventricular outflow tract (RVOT) in children with congenital heart disease have evolved for better durability over the past decades, but conduits failure remains common. We designed decellularized and photooxidatively crosslinked bovine jugular vein conduit (DP-BJVC) and now aim to evaluate the midterm results of DP-BJVC for RVOT reconstruction. Methods: Ninety patients (median age: 4.2 years) undergoing RVOT reconstruction using DP-BJVC were prospectively followed for median of 4.7 years (range: 0.2–16.1 years). Kaplan–Meier analysis was used to examine the survival, freedom from conduit explantation and catheter-based reintervention. Risk factors were analyzed with Cox regression analysis. Results: Follow-up was completed in 92% of patients. There were five (5.6%) early deaths. The 10-year survival rate was 85.2%, with palliative procedure at DP-BJVC implantation as the risk factor. The 10-year freedom from conduit explantation and reintervention were 84.4 and 67.3% respectively, with previous cardiac operation as the only risk factor for explantation. Complications during the follow-up included conduit stenosis (peak gradient ≥50 mmHg) in 12 (12.9%), severe regurgitation in 2 (2.4%), and infective endocarditis in 2 (2.4%). The annual increase in gradient was highest in the first year (P = 0.003), but not appreciably afterwards. The echo-measured annulus diameter trends to increase by an average of 0.37 mm per year. Calcification appeared mild in the failed conduits. Conclusions: DP-BJVC provides satisfactory durability and functionality for RVOT reconstruction for children, with low morbidity of stenosis and endocarditis, as well as increase in diameter mildly with age in midterm follow-ups.